Cyberbullying in Indonesian Female Artist’s Instagram Account: Semiotics Approaches With Psychoanalysis by Carl Gustav Jung - Andriani Febbi Sihite; Citra Anggia Putri (TRANSFORM : Journal of English Language Teaching and Learning, 2023)
In today's digital era, cases of cyberbullying are living in society, especially on social media. Not infrequently also occurs among the public and famous artists. Cyberbullying has various impacts on its victims. This study discusses the behavior of cyberbullying in the development of a developmental digital world using semiotics approaches with psychoanalysis theory of Carl Jung. This study aims to, (a) find out the types of cyberbullying in Indonesia female artist's Instagram account, (b) describe the cyberbullying which existed in the post of Indonesian female artist's instagram account, (c) explain why the particular type of cyberbullying became dominant in Indonesian female artist's instagram account. This study is a qualitative approach. The data source used in this study is taken from Instagram especially about the life content of artist "Prilly Latuconsina" who has been the victims of cyberbullying. The results show that there are various forms of cyberbullying in her instagram account. There are 7 harassment category, 8 denigration category, and 7 flaming category. The netizens often used harsh and impolite words in the comments.